Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s10389-010-0341-y
|View full text |Cite
|
Sign up to set email alerts
|

Linking higher physical activity to lower serum cystatin C among US adults

Abstract: Aim The goal of the study was to examine the association between the intensity of physical activity and serum cystatin C (mg/dl), a novel cardiovascular risk factor. Subjects and method A cross-sectional analysis of a representative sample of the adult US population including 4,510 individuals aged 17 or older and free from heart and kidney disease was conducted. Results A weighted multilinear regression analysis adjusted for age, gender, race, smoking, alcohol intake, body mass index, C-reactive protein, glom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Greenness-related factors, such as physical activity and air pollution, may play a role in the association between greenness and cystatin-C. Evidence suggests that physical activity is associated with lower concentrations of serum cystatin-C ( 32 ). Greenness is also known to have beneficial effects by mitigating the effects of air pollution ( 33 ), which, in the case of kidney function, include elevated cystatin-C concentrations ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Greenness-related factors, such as physical activity and air pollution, may play a role in the association between greenness and cystatin-C. Evidence suggests that physical activity is associated with lower concentrations of serum cystatin-C ( 32 ). Greenness is also known to have beneficial effects by mitigating the effects of air pollution ( 33 ), which, in the case of kidney function, include elevated cystatin-C concentrations ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The potential of thinking with affect matters because of the concerted effort by governments and public health bodies to increase levels of physical activity (Breckenkamp et al, 2004;Faramawi and Caffrey, 2010). However, despite the cautions, participation rates in physical exercise are decreasing across Europe (Hallal et al, 2012).…”
Section: Introduction: Affect and Public Healthmentioning
confidence: 99%
“…The current study is among the first to provide a look at the obesity epidemic from the perspective of WTR. Second, NHANES surveys are large, nationally representative surveys with standardized data collection procedures (Faramawi et al,2010, Faramawi et al,2011, Faramawi et al,2008. Third, waist and thigh measures were obtained by trained study staff using standardized protocols, which avoid the known biases of self-reported body circumferences.…”
Section: Discussionmentioning
confidence: 99%